Comparison of Embodied Carbon of 3D-printed vs. Conventionally Built Houses - Costanza Rossi; Fabian Reitemeyer; Oliver Heidrich; Diego Rybski (Findings)
The construction sector makes a considerable contribution to global greenhouse gas emissions. Considering the ongoing urbanization trends and climate change urgency, the exploration of alternative construction techniques should be a mandate. 3D-printing represents an emergent technology and more and more specimen are being built. We collect data of raw material use for houses that have already been built using 3D-printing. Assessing the construction related emissions, we find that the four examples, for which we could obtain the data, do have less emissions per square meter than conventionally built houses (10 international examples). We argue that 3D-printing represents an interesting alternative, but further research is necessary, not just in terms of environmental implications but also to better understand the social implications, e.g. health and safety or labor.